2022
DOI: 10.4014/jmb.2203.03020
|View full text |Cite
|
Sign up to set email alerts
|

Water Extract of Ecklonia cava Protects against Fine Dust (PM2.5)-Induced Health Damage by Regulating Gut Health

Abstract: To confirm the therapeutic effect of the water extract from Ecklonia cava (WEE) against PM 2.5 induced systemic health damage, we evaluated gut health with a focus on the microbiota and metabolites. Systemic damage in mice was induced through PM 2.5 exposure for 12 weeks in a whole-body chamber. After exposure for 12 weeks, body weight and food intake decreased, and WEE at 200 mg/kg body weight (mpk) alleviated these metabolic efficiency changes. In addition, PM 2.5 induced changes in the length of the colon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The gut and brain are connected through two-way communication called the gut–brain axis [ 12 , 91 ]. Gut microbiome balance and the gut health of hosts have been found to affect the brain through the gut–brain axis [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut and brain are connected through two-way communication called the gut–brain axis [ 12 , 91 ]. Gut microbiome balance and the gut health of hosts have been found to affect the brain through the gut–brain axis [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these changes in the gut microbiome cause neuronal inflammation and apoptosis through dysfunction of the gut–brain axis, causing cognitive impairment such as that found in Alzheimer’s disease (AD) [ 10 , 11 ]. Absorption of PM 2.5 changes the abundance of the gut microbiome and the content of kynurenine metabolites that act as neuronal protection in the gut–brain axis [ 12 ]. Ultimately, damage to the gut–brain axis caused by PM 2.5 can further worsen cognitive dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [39] found that administering the E. cava component dieckol to the inner ear of rats prevented ototoxic hearing loss, suggesting that the procedure may be a safe and effective method to prevent drug-induced hearing loss. Park et al [40] reported that a water extract of E. cava acts as a potential therapeutic agent against fine dust induced health damage in mice by regulating gut function of the microbiota and Kim et al [41] provides evidence for the use of phlorotannin against constipation in rats.…”
Section: Colored Corn Floursmentioning
confidence: 99%